Numerical analysis of gas production from large-scale methane hydrate sediments with fractures. (1st December 2021) - Feng, Yongchang; Chen, Lin; Kanda, Yuki; Suzuki, Anna; Komiya, Atsuki; Maruyama, Shigenao
Abstract: Creating artificial fractures in methane hydrate (MH) reservoirs to improve the reservoir permeability is considered a promising method for realizing high gas production efficiency and recovery rate in MH exploitation. A deep understanding of hydrate dissociation and gas production performance in fractured MH sediments is necessary for practical application of this method. Therefore, a large-scale MH sediment model with a single fracture was developed in this study, and the hydrate dissociation and gas production characteristics and the effect of fracture on depressurization and hot water injection processes were investigated. The numerical results indicate that the fracture in the sediment can significantly improve hydrate dissociation and gas production in the early depressurization stage, and the average gas production rate during the economical production stage increases by 30% in comparison with that without fracture, but it has less effect on the final gas production. Moreover, high fracture permeability would lead to shorter duration of the economical production stage and higher production efficiency. In addition, the fracture is beneficial for hot water to flow deep into the MH sediment, and the production efficiency and final production in the economical production stage increase after injecting hot water along the fracture. Graphical abstract: Schematic diagram illustrating the methane hydrate sediments with fractures and the gas production performance. The figure shows that the creation of artificial fracture can significantly enhance the gas production rate in the early stage, but has less effect on the final gas production. Image 1 Highlights: Gas production from fractured methane hydrate sediments is investigated. Fractures in hydrate sediments are beneficial for enhancing gas production. Hot water can be injected deep into hydrate sediments through fractures. Gas production can be enhanced by pre-hot water injection.